Efficient Fuzzy Logic Based Probabilistic Broadcasting for Mobile Ad hoc Network - Sumit Kumar (International Journal of Computational Intelligence Systems, 2016)
In Mobile Ad hoc networks broadcasting is the one of the most important and crucial phenomenon. Broadcasting can be taken up in many ways and the simplest method of broadcasting is simple flooding which can significantly increase the overheads and can result in redundant messages which can further cause the Broadcasting Strom problem. In this paper, we propose an efficient fuzzy logic based probabilistic broadcasting for AODV protocol in order to reduce overheads. The fuzzy based logic criteria make decisions which are based on some of the important parameters affecting broadcasting like number of neighbors, bandwidth available and remaining energy. The simulation result shows that the proposed algorithm is efficient and reliable with respect to the consumed power, throughput, overhead, collision rate and it also maintains low normalized routing load as compared to AODV and other routing protocols proposed in the literature in which simple flooding or fixed probability broadcasting is used.